Hydrological centre for tropical rain zones - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
UNESCO will open a centre for research on the problems of water resources in Latin America and the Caribbean in Panama City, as a result of an agreement signed on 13 November, 1992 in Paris. It will be called CATHALAC (Centro del Agua del Tropico...